The pedagogy of Porter: The origins of the Reformatory in the Cape Colony, 1882-1910 - Chisholm, Linda (My University, 1985)
This article explores the origins and nature of the reformatory in Cape colonial society between 1882 and 1910. Borne in a transitionary period, its concern was with the reproduction of a labouring population precipitated by colonial conquest. Unlike the prison and compound, which gained their distinctive character from the way in which they were articulated to an emerging industrial capitalist society, the reformatory was shaped by the imperatives of merchant capital ad commercial agriculture. The internal operations were structured by an ideology of rehabilitation through institutionalisatlon and socialisation and by the particular material conditions of the Western Cape, although the segregationist reverberations of the industrial revolution were also heard 'at a distance'. These issues conditioned, and were refracted throgh the internal structure and discipline of the reformatory, the relationship between education and work, between the reformatory and the labour market, responses of the inmates and attempts by the authorities to control these by, inter alia, a strategy of racial segregation.
African Studies Seminar series. Paper presented 30 April, 1985
Keywords: Reformatories. South Africa; Juvenile delinquency. South Africa; Porter Reformatory (South Africa)